Interactions between fig wasps and their host figs - Nefdt, Rory John Charlton (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1990)
Fig trees (Ficus spp.) and fig wasps (Hymenoptera: Agaonidae) are partners in an intimate mutualism. The trees provide ovules in which wasp larvae develop while the wasps pollinate the flowers and are therefore indispensible for fig seed production. Agaonid fig wasps oviposit down the styles of fig flowers and it has generally been accepted that they were unable to reach the ovules of "long" styled flowers , which would produce seeds, thus maintaining an evolutionary stable mutualism. African fig species were found to have unimodal style length frequencies, with no separation into long and short styled flowers. In several species the ovipositors of their associated agaonids were long enough to reach the majority of ovules. The number of foundress agaonids entering a fig influenced fig seed set and therefore was an important factor regulating the proportion of flowers producing seeds or pollinators. In the two Ficus species that were studied, entry of more than three agaonid foundresses into one fig resulted in competition for limited oviposition sites and less female - biased offspring sex ratios. It is hypothesised that sequential laying of male eggs followed by female eggs, under variable oviposition site limitation, results in sex ratio adjustment, as predicted by local mate competition theory. Evidence in support of this hypothesis is presented. A number of non - pollinating torymid and pteromalid fig wasps also oviposit into each fig species. The sycophagines and sycoecines oviposit down the styles from inside the fig inflorescences like their agaonid counterparts, while other species insert their ovipositors through the wall of the fig from the outside. Like the agaonids, sycophagines were characterised by being pro - ovigenic, with numerous fully developed eggs at emergence. Sycoecines were able to re - emerge from figs they had oviposited in and lay their eggs in more than one fig. They had short ovipositors, allowing access to a smaller proportion of flowers than agaonids or sycophagines. Externally ovipositing fig wasps were syn-ovigenic, able to develop eggs as adults and invested more energy and time during each oviposition event. Differences in the ovipositor lengths of these species did not segregate their oviposition sites spatially, and therefore does not reduce competition between species. Attack by parasitoids and inquiline fig wasps from the exterior did not constitute a selection pressure against agaonids ovipositing in ovules closer to the periphery of the fig's surface, as predicted by Michaloud's enemy-free-space hypothes is. It cannot therefore explain the preference shown by ovipositing agaonids for shorter styled flowers.
Keywords: Wasps; Mutualism (Biology)